STRATEGI FORESIGHT LEADERSHIP KEPALA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER JABAR MASAGI (Jurnal Tata Kelola Pendidikan, 2020)
This study entitled Principal Foresight Strategy in Implementation of Character Education“Jabar Masagi” at state Vocational High School (SMKN) 1 Bandung. The problem thatthe authors have addressed in this study is about foresight strategy and implementation ofcharacter education “Jabar Masagi”. This research aims to find out how Principalimplements Foresight Leadership Strategy in Character Education “Jabar Masagi” atSMKN 1 Bandung. This study use qualitative descriptive approach. Subjects of this studywere a principal, teachers, and students. The data was obtained by interview anddocumentation study and were analyzed by reducing the data, presenting the, andconcluding the data in in narrative form. The result of the study reveal that: 1) SMKN 1Bandung has already implement Character Education “Jabar Masagi” since December2018. The integration of each value in the Character Education “Jabar Masagi” at SMKN1 Bandung were carried out by habituation method, the principle and teachers guidanceby showing the students some set of an example, teaching and learning activity and alsoextracurricular activity. The implementation will not be separated by the role of theprinciple, teachers students and their parents. 2) In designing their future plans, principleanalyze the outcome from the past experience, the outcome that met school standard andthe outcome that did not met the school standard in order to get a better outcome in thefuture. 3) According to the characteristic of Foresight Leadership which the principlepossessed, principle designing the plan to implement Character Education Program“Jabar Masagi”, any programs that related to Character Education “Jabar Masagi” wereimplemented by habituating the students, tutoring or counseling, and also by giving themsome set of an example
Keywords: Foresight Leadership; Character Education